Energy sustainability in the transport sector using synthetic fuels in series hybrid trucks with RCCI dual-fuel engine. (15th January 2022) - García, Antonio; Monsalve-Serrano, Javier; Lago Sari, Rafael; Martinez-Boggio, Santiago
Highlights: Experimental transient evaluation of Reactivity controlled compression ignition engine. Optimum configuration of a series hybrid low temperature combustion truck. Synthetic fuel in order to achieve low Well-to-Wheel CO2 emissions in trucks. Homologation and real driving conditions considered for the results analysis. Abstract: The green-deal carbon neutrality target set for 2050 and CLOVE consortium predictions of NOx reductions confirm the efforts of the European commission to achieve a clean and sustainable transportation. In this sense, several solutions are needed to fulfill with the short-term regulation requirements and provide a sustainable transportation transition. This work assesses the potential and challenges of using a Reactivity Controlled Compression Ignition, RCCI, engine in a series hybrid medium duty truck fueled with both conventional and synthetic. The numerical results enabled to design the hardware and control system of the concept. Experimental results show a good agreement with numerical simulation estimation with CO2 tailpipe below 3%. Overall, using diesel and gasoline, it is possible to fulfill the current EUVI regulation without after-treatment while promoting benefits of more than 10% in CO2 Tank-to-Wheel emissions. The use of Oxymethylene Dimethyl ethers, OMEx, instead of diesel allows further reductions of both NOx and soot emissions due to its no carbon-to-carbon bonds and higher oxygen content. The Well-to-Wheel CO2 analysis shows that OMEx-Gasoline operating as series hybrid achieves above 25% of CO2 benefits against current commercial truck.